From Thinking to Designing: How Habits of Mind and Perceived Teacher ESD Competence Shape Pre-service Teachers' ESD Instructional Materials - Bambang Ekanara; Ilma Riksa Isfiani (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
Future biology educators face a unique challenge when creating learning modules for Education for Sustainable Development (ESD): they must seamlessly fuse core biological science with broader sustainability values. To understand what drives success in this complex task, we explored how two internal factors—Habits of Mind (HoM) and Perceived Teacher ESD Competency—shape the way pre-service teachers craft their instructional designs. We approached this through an explanatory sequential mixed-methods framework. Initially, we gathered quantitative survey data from 49 prospective teachers in Indonesia. Building on those baseline numbers, we then dove deep into the qualitative experiences of nine selected individuals by analyzing their module documents, reflective journals, and semi-structured interview transcripts. Our statistical modelling showed a strong relationship: together, these cognitive and psychological traits accounted for 64.3% of the differences in module quality (R^2=0.643, p